2023
DOI: 10.1021/acsanm.3c02147
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Oxygen Vacancies in CeO2 Nanostructures for Catalytic Aerobic Cyclohexane Oxidation

Abstract: Nanostructured cerium-based catalytic materials have attracted much attention in the field of redox catalysis, due to the excellent active sites exposed on the nanocrystal surface, and herein, the oxygen vacancy (O V ) and the crystal facet effect of typical model nanostructured ceria (Nano-CeO 2 ) were focused and investigated for the catalytic aerobic cyclohexane oxidation. Specifically for the CeO 2 nanocubes with a {100} facet, the CeO 2 nanopolyhedrons with a dominant {111} facet, and the CeO 2 nanorods w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The two peaks desorbed below 450 °C are usually considered as ROS (such as O 2 2– , O 2 – , or O – ) of Co 3 O 4 catalyst, and the active oxygen on the surface of the catalyst plays an important role in promoting the catalytic oxidation reaction . ROS, with a peak at 100 °C, has the lowest desorption temperature, which is easy to obtain and participate in cyclohexane oxidation conditions, and O 2 – is an oxygen that can be obtained by obtaining only one electron . It is considered that the desorbed O 2 – at this temperature is the main active species involved in cyclohexane oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two peaks desorbed below 450 °C are usually considered as ROS (such as O 2 2– , O 2 – , or O – ) of Co 3 O 4 catalyst, and the active oxygen on the surface of the catalyst plays an important role in promoting the catalytic oxidation reaction . ROS, with a peak at 100 °C, has the lowest desorption temperature, which is easy to obtain and participate in cyclohexane oxidation conditions, and O 2 – is an oxygen that can be obtained by obtaining only one electron . It is considered that the desorbed O 2 – at this temperature is the main active species involved in cyclohexane oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…− is an oxygen that can be obtained by obtaining only one electron. 34 It is considered that the desorbed O 2 − at this temperature is the main active species involved in cyclohexane oxidation. Compared with Co 3 O 4 -P, the O 2 desorption peak of Co 3 O 4 -C below 450 °C obviously moves to the low-temperature region, which means that the surface oxygen vacancies are more likely to activate the adsorbed oxygen, and the nanocage framework of Co 3 O 4 -C can construct an internal and external concentration gradient, resulting in a limited space to provide a local high concentration of O 2 when adsorption and desorption occur in the cage, resulting in easier activation of oxygen to form ROS.…”
Section: Surface Chemical States Of Catalystsmentioning
confidence: 99%
“…Aerobic oxidation of hydrocarbons is of great importance for producing value-added oxygenated chemicals in the modern chemical industry. , Among them, the selective oxidation of saturated alkanes under mild conditions is much more difficult due to the laborious activation of inert C–H bonds and facile deep oxidation of reactive target products. , For example, cyclohexane liquid-phase oxidation into cyclohexanol, cyclohexanone, and adipic acid, a typical hydrocarbon resource high-value utilization process, is the crucial technology to manufacture polyamide 6 and 6,6 in industry. , In general, the oxidation of cyclohexane with molecular oxygen is performed in the presence of soluble metal salts at the temperature of above 150 °C, wherein the cyclohexane conversion is controlled below 4% to maintain the overall selectivity toward cyclohexanol and cyclohexanone at a relatively high level of 70–85%. , The serious energy consumption and increased environmental concerns call for benign oxidation including high oxidation efficiency, recoverable catalysts, molecular oxygen as the green oxidant, and solvent-free. In the past decade, the solvent-free cyclohexane oxidation has been paid more attention in developing new types of heterogeneous catalysts. , Diverse metal and metal oxide catalysts have been developed and applied into the catalytic oxidation of cyclohexane. Among them, metallic cobalt and cobalt oxides (e.g., Co 3 O 4 , LaCoO 3 , and Co-MgAlO) with the adjustable structure properties are widely considered as the promising catalysts for the cyclohexane oxidation by adsorbing and activating O 2 molecules or C–H bonds in cyclohexane on the active sites. Nevertheless, Unnarkat et al and Yuan et al found that organic acids and water generated in the course of the cyclohexane oxidation were inclined to adsorb on the active sites, giving rise to the inevitable deactivation of the catalysts. , Thus, it can be found that there are two core issues to be addressed for the heterogeneous catalytic oxidation of cyclohexane: (i) to ensure the acceptable product selectivity (above 90%) at the relatively high conversion (above 15%) under mild reaction conditions and (ii) to construct the robust catalytic structure against the deactivation during oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al 16 reported that the synergistic effect between CeO 2 and MnO x could provide more amounts of oxygen vacancy, the highest concentration of Mn 3+ , and the highest Ce 3+ contents, which resulted in an outstanding oxygen mobility, causing the improvement of catalytic activity. Li et al 17 reported that cerium dioxide nanoparticles have the most active surface oxygen vacancies that determine the catalytic activity and have the strongest activation capacity, contributing to high reactivity under extremely inert conditions. The roasting process of vanadium slag is a typical oxidation process, and the activation of molecular oxygen has emerged to be an important step.…”
Section: Introductionmentioning
confidence: 99%